Le Parménide de Platon : une cosmologie sans kosmos ? - Gabrièle Wersinger Taylor (Études Platoniciennes)
The aim of this paper is to question the absence, in the second part of Plato’s Parmenides, of the word kosmos and kindred words such as diakosmos etc., whereas they are frequent in others Plato’s dialogues, a question all the more necessary if one admits that this second part should be understood as a “toolbox for cosmology” as Luc Brisson has rightly showed. One may be astonished about such an absence whereas the study of the relevant texts concerning the historical Parmenides reveals that he uses such words as kosmos and diakosmos. Now the study of this second part shows that the use of opposites obeys a logic of enantiomorphic, antilogic, heuristic and circular affections (pathé) and that the eight hypotheses are based on a systematic combinatory use of opposites, the mechanism of which is the radical opposition between separation and radical participation, an opposition which is invalidated by the Sophist.The comparison with the Sophist, the Timaeus, and the Philebus, makes it possible to tell why the enantiomorphic logic of the pathemic participation is sterile. It is so because it fails to reconcile the contraries in a selective and musical “sumplokè” capable of building a kosmos involving a mathematical model (logistikè) that could establish a medium between the opposites. Parmenides’ model functions as a repellent for this kosmological model, the inspiration of which is Pythagorean (whether it is Plato’s fiction or not is not a question we shall enter here) because, among all, it lacks of harmony and music by privileging diakrisis and the goddess Necessity, associated to parturitions incapable of generating a kosmos.